(untitled) (Journal of Engineering and Health Sciences, 2017)
This paper is a report of a study conducted to identify stress difference between male and female nursing student and to examine the relationship between levels of stress in nursing student with their gender during clinical posting. The study used quantitative design analyses to examine relationship between independent variable [gender (male, female)] and dependent variable (stress level). This study was carried out with 150 participants from semester 1 year 1 till semester 1 year 3 throughout 3 years of nursing diploma programme at College University Islam Melaka (70% response rate). The data were collected over a month. Results shows that stress level among student nurses are varies from low to medium during clinical posting. But mostly student nurses experiences medium stress level during clinical posting. Comparing with stress level between both gender shows that there is no difference in level of stress between both gender and relationship between level of stress and both gender shows that it is found that significant value for gender between male and female student nurses is 0.435 more than significant value of 0.05. These shown that there is no significant relationship level of stress to gender in nursing student.